The effect of femoral shortening in the treatment of developmental dysplasia of the hip after walking age - Castañeda, P. (J Child Orthop, 2019)
PURPOSE: The optimal treatment for late-presenting developmental dysplasia of the hip (DDH) is controversial. High tension forces after hip reduction increase the pressure on the femoral head, potentially causing avascular necrosis. Femoral shortening (FS) is commonly used as a means to decrease the pressure on the femoral head. We examined the effect of FS on the outcomes of patients with late-presenting DDH. METHODS: A total of 645 hips of a late-presenting DDH cohort treated with open reduction and iliac osteotomies were retrospectively reviewed; 328 hips had a FS performed (FS+) and 317 (FS-) had not. The mean age was 3.9 years (sd 1.55). We classified the hips with the Tönnis and International Hip Dysplasia Institute (IHDI) methods; and the Pediatric Outcomes Data Collection Instrument (PODCI), Iowa Hip Score (IHS) and Severin classification as outcome measurements. RESULTS: The FS- group had higher scores in PODCI (median 95 points; interquartile range (IQR) 78 to 91) and IHS (median 91 points; IQR 64 to 88) than the FS+ group (PODCI: median 94 points; IQR 69 to 89 points; IHS: median 89 points; IQR 62 to 87). The mean Severin scores were similar (FS- 2.65; FS+ 2.5; p = 0.93) but the FS– group had higher rates of good and excellent outcomes (FS- 56%; FS+ 41%; p < 0.00001) and lesser dislocation rates (FS- 6%; FS+ 14%; p = 0.16). CONCLUSION: Although FS should be used when a hip cannot be reduced without undue tension, our results indicate that this procedure is not necessarily related to a better outcome. LEVEL OF EVIDENCE: Therapeutic, Level III.